Reinventing regional security institutions in Asia and Africa : power shifts, ideas, and institutional change - Koga, Kei (New York : Routledge Taylor & Francis Group, 2017)
'Regional security institutions play a significant role in shaping the behavior of existing and rising regional powers by nurturing security norms and rules, monitoring state activities, and sometimes imposing sanctions, thereby formulating the configuration of regional security dynamics. Yet, their security roles and influence do not remain constant. Their raison d'etre, objectives, and functions experience sporadic changes, and some institutions upgrade military functions for peacekeeping operations, while others limit their functions to political and security dialogues. The question is: why and how do these variances in institutional change emerge? This book explores the mechanisms of institutional change, focusing on regional security institutions led by non-great powers. It constructs a theoretical model for institutional change that provides a new understanding of their changing roles in regional security, which has yet to be fully explored in the International Relations field. In so doing, the book illuminates why, when, and how each organization restructures its role, function, and influence. Using case studies of the Association of Southeast Asian Nations (ASEAN), the Economic Community of West African States (ECOWAS), and the Organization of African Unity (OAU)/African Union (AU), it also sheds light on similarities and differences in institutional change between regional security institutions'--
Theory of institutional change in regional security institutions -- Association of Southeast Asian Nations (ASEAN) -- Economic Community of West African States (ECOWAS) -- The Organization of African Unity (OAU)/African Union (AU) -- Dynamics of institutional change in RSIs.
Includes bibliographical references (pages [182]-218) and index.
Keywords: Security, International -- Asia; Security, International -- Africa; Organizational change -- Asia; Organizational change -- Africa; Asian cooperation; African cooperation